Initial Dynamics of Financial Markets in the Transition Economies in the 1990s and New Critique of the Big Bang Policy: Heterodox Approach - Rozmainsky, I.V. (Економічний вісник Донбасу, 2010)
Heterodox — Post Keynesian and Institutionalist — economics proves that expansion of financial sector can be harmful for the real sector. Such conclusion is an effect of account of variability of preferences, planning horizons and degree of rationality in the behavior of economic agents. We suppose that both methodology and conclusions of Heterodox Economics can be especially topical for many transition economies. The point is that fundamental features of the transitional economies affect the patterns of choice of agents in the financial markets. These patterns, in turn, lead to the adverse effects of the expansion of financial markets in such economies. Key words: Financial Markets; Transitional Economies; Economics of Transition; Rationality; Heterodox Economics.